(untitled) (Research, Society and Development, 2022)
The current global health situation recently marked by the COVID-19 pandemic has had impacts affecting morbidity and mortality rates. The population with some type of mental disorder suffered consequences in this scenario, such as the difficulty of accessing some health service. Thus, this study aimed to identify the main findings in the literature about how access to health services for people with mental disorders was being carried out during the pandemic period. This is an integrative literature review, where the data collection was carried out in December 2021 in the Virtual Health Library, identifying 108 articles, which after analyzing the inclusion criteria resulted in 05 eligible articles. The publications showed the predominance of virtual care services with electronic devices. And this form of access to health services had advantages such as flexible scheduling and reduced waiting time, as well as disadvantages, such as technological (internet access) and communication barriers, among others mentioned. Thus, the importance of implementing measures that enhance access to health services for the population with mental disorders is perceived, whether remotely or in person, in order to prioritize comprehensive care for the population’s health.